EVALUATION OF AN ISLAMIC VALUES–BASED PERFORMANCE APPRAISAL SYSTEM FOR EDUCATIONAL PERSONNEL IN MADRASAH ALIYAH TO IMPROVE THE QUALITY OF EDUCATIONAL SERVICES - Mawardi Mawardi; Fatmi Ramlah; Muslimin Muslimin; Mariana Mariana (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
Performance appraisal of educational personnel plays a strategic role in ensuring service quality and institutional accountability in educational organizations. In Madrasah Aliyah Negeri (MAN), however, performance appraisal practices for non-teaching staff are often conducted informally and are weakly integrated with Islamic value-based management principles. This study aims to evaluate the performance appraisal system for educational personnel in Madrasah Aliyah Negeri based on Islamic values and to examine its implications for improving educational service quality. Employing a qualitative evaluative approach, the study was conducted in a Madrasah Aliyah Negeri in Sarolangun Regency, Jambi Province. Data were collected through in-depth interviews, document analysis, and non-participant observation involving educational personnel and institutional leaders, and were analyzed thematically. The findings reveal that Islamic values such as amanah (trustworthiness), justice (‘adl), responsibility (mas’uliyyah), and ihsan (excellence) are present mainly as implicit moral expectations rather than as formal performance indicators within the appraisal system. Performance evaluation practices rely heavily on leadership supervision, lack standardized instruments, and are weakly linked to systematic follow-up actions for service quality improvement. As a result, performance appraisal contributes to short-term behavioral compliance but has limited impact on sustainable service quality and quality assurance mechanisms. This study concludes that strengthening educational service quality in MAN requires a formalized, standardized, and value-integrated performance appraisal system. By operationalizing Islamic values as measurable performance constructs and aligning appraisal outcomes with quality assurance processes, performance appraisal can function as a strategic instrument for continuous service improvement in Islamic secondary education institutions.